2001
DOI: 10.1046/j.1365-2958.2001.02615.x
|View full text |Cite
|
Sign up to set email alerts
|

The att locus of Rhodococcus fascians strain D188 is essential for full virulence on tobacco through the production of an autoregulatory compound

Abstract: SummaryThe ability of Rhodococcus fascians strain D188 to provoke leafy gall formation on a variety of plant species is correlated with the linear plasmid pFiD188, on which different pathogenicity loci were identified. The att locus affects the severity of symptom development on tobacco, whereas the fas locus is essential for virulence. To gain insight into the function of the att locus, sequence and expression analyses were performed. The att locus contains nine open reading frames homologous to arginine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 52 publications
(56 reference statements)
1
61
0
Order By: Relevance
“…In this context, it is interesting that the augmentation of Trp was one of the highest measured. Production of the autoregulatory compound by the att locus involves Arg biosynthesis, and expression of the att genes is inhibited by Orn and Arg (Maes et al, 2001). Again, it is remarkable that the concentrations of these amino acids were lower than those of the controls at the onset of the interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is interesting that the augmentation of Trp was one of the highest measured. Production of the autoregulatory compound by the att locus involves Arg biosynthesis, and expression of the att genes is inhibited by Orn and Arg (Maes et al, 2001). Again, it is remarkable that the concentrations of these amino acids were lower than those of the controls at the onset of the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transcript and metabolite data indicated that the flux through the TCA cycle was also reduced when the disease became fully established, although the concentration of succinate remained high throughout the interaction and pyruvate levels were elevated at the early stages of infection. Interestingly, virulence gene expression in R. fascians is induced by an autoregulatory compound and the induction levels are significantly increased in the presence of succinate and pyruvate (Temmerman et al, 2000;Maes et al, 2001). The decreasing amounts of Ser and Gly, together with the increase in glycerate levels, may point to photorespiratory Gly decarboxylation that would add to the reduced photosynthetic and TCA cycle activities (Atkin et al, 2000;Raghavendra and Padmasree, 2003;NunesNesi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial isolates had always been grown in relatively rich media, but from recent insights, we know that essential virulence genes are not expressed under these conditions (22,27,32). Therefore, we determined the CK profiles of strain D188 and its plasmid-free derivative D188-5 as reference, grown in defined minimal medium optimized for virulence gene expression (22).…”
Section: Discussionmentioning
confidence: 99%
“…The fasA-F and the fasA-D regions were amplified via PCR from genomic DNA of strain D188 with the primer pairs fasAstart-fasFend and fasAstart-fasDend (Supplementary Table 1), respectively, and cloned as XbaI/HindIII fragments into pRF37 (a bifunctional cloning vector for R. fascians) (Desomer et al 1990), yielding the cloning intermediates pRF37fasA/F and pRF37fasA/D. The promoter of the att operon of R. fascians (Maes et al 2001) was amplified via PCR from genomic DNA of strain D188 with the primers attpromstart and attpromend and cloned as an XbaI fragment into pRF37fasA/F and pRF37fasA/D, yielding the final constructs pRF37fasOE-A/F and pRF37fasOE-A/D. These plasmids were introduced into D188-fas5 and D188-fasD ) via electroporation and selection on phleomycin (Desomer et al 1990).…”
Section: Construction Of Overexpression Plasmids and Generation Of Famentioning
confidence: 99%